Pengolahan Surat Masuk Dan Surat Keluar Pada Mts Sholihiyyah Management Inbox and Outbox of MTs Sholihiyyah (Information Technology and Telematics, 2015)
ABSTRACT Management Inbox and Outbox of MTs Sholihiyyah still using manual processes. In filing a letter, the officers are still writing data inbox and outbox mail in the agenda book. So that the management manual has many weaknesses, among others: the difficulty in control processing of letters, data errors due to human error, the difficulty of the search letter when will be needed, untidiness documentation of data, loss of mail due to scattered, and the reporting process should be long and complicated , Associated with the development of information technology is growing rapidly, it takes the application for processing correspondence so that more time efficient and can be organized. This letter processing application has been designed using the programming language PHP and MySQL. So that later can be implemented with a facility that will provide ease in processing and archival letters. Keywords: letters, archives, PHP, MySQL